Analyzing The Role of Earning Management in Mitigating Going Concern Risk: Empirical Study of Indonesian Banking Companies - Egi Gumala Sari; Febriyanti, Nabilah; Hotang, Keri Boru; Yusuf Faisal (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This research aims to obtain empirical evidence about the influence of company growth, financial distress, opinion shopping, and political costs on going concern audit opinion with earnings management as a moderating variable. This research uses a quantitative type of research. The sample in this study was 33 banking sub-sector companies listed on the Indonesia Stock Exchange in 2014-2023. The analysis technique used to test the hypothesis is multiple regression analysis using Eviews 9 software. The results of this study found that Company Growth has a negative and statistically significant effect on Going Concern Audit Opinion, as well as Financial Distress has a negative and statistically significant effect on Going Concern. Audit Opinion, while Opinion Shopping has a positive and statistically insignificant effect on Going Concern Audit Opinion, Political Cost has a positive and statistically significant effect on Going Concern Audit Opinion, and Earnings Management has a negative and statistically significant effect on Going Concern Audit Opinion. Then, Earnings Management strengthens the influence of Company Growth on Going Concern Audit Opinion, likewise Earnings Management does not strengthen the influence of Financial Distress on Going Concern Audit Opinion, besides that, Earnings Management strengthens the influence of Opinion Shopping on Going Concern Audit Opinion, and Earnings Management does not strengthen the influence of Company Growth towards Going Concern Audit Opinion